Differences of inflammatory cytokine profile in patients with vulnerable plaque: A coronary CTA study - Roesner, Caroline; Göller, Markus; Raaz-Schrauder, Dorette; Dey, Damini; Kilian, Tobias; Achenbach, Stephan; Marwan, Mohamed; Bittner, Daniel O. (Atherosclerosis, 2022)
Background and aims: Various pro-and anti-inflammatory biomarkers are involved in the process of atherosclerosis. We analyzed the association of different biomarkers with coronary plaque volume and vulnerable plaque subcomponents. Methods: In 301 patients undergoing coronary CT angiography (CTA), total coronary plaque volume (TPV) and subcomponents including non-calcified plaque volume (NCPV) and vulnerable plaque burden were quantified using semi-automated software. Serum was analyzed for various cytokines. Results: Out of 301 patients, 207 (69%) were male. The mean age was 59 +/- 10 years. Patients were divided using the median of TPV, NCPV and vulnerable plaque burden. In univariable analysis, patients with high TPV, high NCPV and high vulnerable plaque burden showed significant higher serum levels for IFN?, IL-1a,-2,-4,-10 and-17 and significant lower levels for IL-8 and MCP-1 (all p < 0.05). Multivariable analysis showed positive associations between high vulnerable plaque burden, IL-1a (OR 2.60, p = 0.001) and Eotaxin (OR 1.89, p = 0.020), and inverse association to MCP-1 (OR 0.33, p < 0.001), independent of age, gender and CVRF. In exploratory subanalyses, patients with presence of atherosclerosis (n = 247; 82%) showed significantly higher levels of IL-17 in all subgroups with high vulnerable plaque burden, irrespective of overall plaque volume (all p < 0.001). Conclusions: The cytokine profile significantly differs between patients with high and low coronary plaque volume. IL-1a and IL-17 seem to play a major proatherogenic role in vulnerable plaque formation, whereas MCP-1 paradoxically portends protective effects. Longitudinal studies with serial cytokine testing are needed to identify potential targets for therapeutic interventions.
CRIS-Team WoS Importer:2022-06-24
Keywords: Inflammatory biomarkers; Interleukin; Atherosclerosis; Coronary CT-angiography; Plaque volume; Vulnerable plaque